NEGOSIASI DAKWAH DAN POLITIK PRAKTIS (MEMBACA ORIENTASI ORGANISASI SAYAP KEAGAMAAN ISLAM PADA PARTAI NASIONALIS) - Kusuma, Bayu Mitra Adhyatma; Octastefani, Theresia (al-Balagh : Jurnal Dakwah dan Komunikasi, 2017)
Islam is a da’wah religion which disseminate the truth. But on the other hand, Islam is a political religion that is often used as the basis of ideology and struggle in the democratics era that upholds the constitution. Nowadays Muslims have various political channels through Islamic political party. But each Islamic party has different interests although equally portray itself as the da’wah party or Indonesian Muslim political home. In the dynamics, political behavior by using da’wah symbols and labeling was also performed by parties with nationalist genealogy like Partai Demokrasi Indonesia – Perjuangan, Partai Golongan Karya, and Partai Demokrat through the Islamic religious wing organization. One actual case we can make a referral is the DKI Jakarta governor election. That phenomenon is authentic evidence that the negotiation between da’wah and practical politics is happen. To deepen the phenomenon, this study used qualitative types, descriptive approach, and interactive data analyst methods by Miles and Huberman. The research results showed that the da’wah agendas which organized tends to be incidental to adjust with the political constellation that they face and optimized just ahead of key moments in the political calendar like regional head election. It can be concluded that the orientation of Islamic religious wing organization by nationalist political party are more on political da’wah rather than da’wah politics. So that in the negotiations between da’wah and practical politics, the political aspect is more advantaged than the da’wah aspect.